ORGANIZATIONAL AMBIDEXTERITY: KETANGGUHAN YANG DIBUTUHKAN UNTUK KEBERLANGSUNGAN KINERJA ORGANISASI MASA DEPAN - Retno Sari, Santi (Economic Faculty, Attahiriyah Islamic University, 2017)
Organizational ambidexterity has emerged as a new research paradigm in organizational theory, but some fundamental issues in this debate remain controversial. Ambidexterity is the ability to exploit existing capabilities and to explore new opportunities. Achieving exploitation and exploration enables organizational success, even organizational resilience to improve and maintain sustained superior performance, but creates tensions and challenging. The ambidextrous organization excels in utilizing existing products to enable additional innovation and to explore new opportunities to drive more radical innovation, but related research is limited. This article aims to advance our understanding of the prerequisites of organizational prerequisites, approaches to achieving them, and to address the impact of each level of individuals and organizations for the sustainability of ambidexterity organizational achievements keywords: organizational ambidexterity, exploration-exploitation.